Cervical human papillomavirus genotypes in a high HIV setting: A scoping review of a decade of human papillomavirus epidemiological research in Botswana - Tawe, Leabaneng; Ramatlho, Pleasure; Ketlametswe, Rebecca; Koobotse, Moses; Robertson, Erle S.; Grover, Surbhi; Ramogola-Masire, Doreen; Paganotti, Giacomo M. (Frontiers in Medicine, 2022)
Cervical cancer burden is still high in low- and middle-income countries, including Botswana. Persistent human papillomavirus (HPV) infection is the leading cause of cervical cancer. Accurate knowledge of HPV diversity associated to cervical cancer in sub-Saharan Africa may provide accurate understanding of the natural history of HPV infection in these contexts. The goal of this review was to consolidate existing evidence on cervical HPV infection and to conduct a pooled analysis of data from all eligible Botswana studies. After a successful review of twelve studies on cervical HPV genotypes that met the inclusion criteria, HPV-16 genotype was the most frequently discovered in women with pre-cancerous and cancer lesions, followed by HPV-18. HPV-16 in HIV-positive women with precancerous lesions to cancer is between 45% and 47.7%, and between 4.5% and 26.1% for HPV-18. With reference to other HPV genotypes, the proportion of HPV-35 and HPV-58 (13-16%) seems relatively consistent among the studies, however HPV-58 appears to be more common in HIV-positive subjects compared to HIV-negative women. Indeed, HPV-45 seems to be frequently detected in women with cervical cancer compared to women with precancerous lesions. Regarding the low-risk HPV genotypes, an appropriate breakdown has been provided. In conclusion, the current prophylactic vaccines against HPV-16 and HPV-18, which have demonstrated good immunogenicity in HIV-infected populations, may still prevent infection and ultimately cancer.